Promocje doktorskie jako ceremonie akademickie - Szymczak, Emilia (Studia Edukacyjne, 2018)
Academic regalia, symbols and ceremonies are an important element of university reality. The ruling force here is the tradition and continuity of the preservation of symbols since the Middle Ages. The awarding of academic degrees and titles in the XXI century is still associated with a consistent structure during which specific rituals – characteristic for University or even each field of study – take place. They become an exemplification of prestige in the academic world, the position of professors, as well as other social groups, and crystallize the place in the hierarchy of various individuals and groups of people, as well as the academic capital that they represent. In this article, I will focus on this initial level of academic career which is a doctorate and especially at this ceremonial or symbolic ritual of passage – the doctoral promotion.